Role of Supply Chain Management on Prevention of Crude Oil and Gas Company’s Value Decreasing in Oil Price Falling Period: Evidence from Indonesia - Dormauli Justina; Alex Johanes Simamora (International Journal of Supply Chain Management, 2018)
This research is aimed to examine role of supply chain management in prevent companys value decreasing in oil price falling period. This research use nine crude oil and gas companies listed in Indonesian Stock Exchange from 2013-2016 as research sample. Based on fixed effect regression, supply chain management weakens negative effect of oil price falling on companys value. It indicates that by implementing better oil demand forecast; company reduces overload production and inventory cost, integrating function of drilling contract, demand forecasting, maximization of assets utilization; good supply chain management helps company to prevent value decreasing in oil price falling period. This research has implication to management to formulate excellent supply chain strategy in order to make company survive in oil price collapse.